Community Group Participation in Maintenance of Cengklik Reservoir as a Water Resources Conservation Area - Aulia Dwi Nurmalasari; Yosafat Hermawan Trinugraha; Septina Galih Pudyastuti (Jurnal Ilmiah Platax, 2023)
Reservoirs are water resources that function for the needs of the community. Reservoir maintenance is carried out to maintain the conservation of water resources and inhibit sedimentation. This study aims to determine the participation of the Ngudi Tirto Lestari community group in Sobokerto Village in maintaining the Cengklik reservoir. This research uses the theory of community participation according to Keith Davis with 3 indicators: individual mental and emotional involvement, motivation to contribute, and individual responsibility. The method used is qualitative with a descriptive approach. Data collection is done by observation, interview, and literature study. The results of the study are Community Group Participation in maintaining the Cengklik reservoir as a water resource conservation area in Sobokerto Village is quite good. In individual mental and emotional involvement, community groups are aware of social activities and the important benefits of maintaining the Cengklik reservoir. The encouragement of contribution motivation, community groups received encouragement from the Sobokerto Village government and PT Pertamina Patra Niaga Adi Soemarmo through socialization and training activities regarding reservoir maintenance. However, there is still a lack of responsibility for reservoir maintenance caused by the collision of other individual activities, so it is necessary to hold bounding between members.